(untitled) (Research in Agriculture Livestock and Fisheries, 2016)
Industrial fishing in Bangladesh is operated by wooden trawler (ice trawler) and steel made trawler known as freezer trawler. There is significant lack of valuable information on freezer trawler fishing data though it contributes a remarkable portion in national marine capture fisheries which is not negligible. This study aims to investigate the historical trends in freezer trawler fishing of Bay of Bengal. Data from different sources were compiled and analyzed to complete this study. A total of 91 industrial freezer trawlers were recorded from the deep-sea fishing industry in Bangladesh. 72 of them are fish trawlers and 19 are shrimp trawlers. In 1990, there were only 5 freezer trawlers with a total capacity of 490 ton which increased up to 21,737 ton in 2014 by 91 trawlers. The calculated production of marine capture fisheries by freezer trawlers increased from 2940 ton (1990) to 150113 ton (2014) that is about 1 to 21 % of the FAO landings and 0.5 to 12 % of the reconstructed total national production of marine capture fisheries respectively. A total of 1.83 million ton of fisheries products were captured from the Bay of Bengal in last two decades (1990- 2014). This study output will be helpful as a baseline database of freezer trawler for marine capture fisheries in Bangladesh. Res. Agric., Livest. Fish.3(1): 217-226, April 2016